PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM GERAKAN DESA IKUT SEJAHTERA (GADIS) DI KABUPATEN PESAWARAN - Kaligis, Dendy Romadhona; Syafri, Wirman; Achmad, Mansur (UIR PRESS, 2021)
This research departed from the problem of organizing the GaDIS program, the Pesawaran District Government formed the GaDIS Financial Aid Coordination Team as the organization implementing GaDIS assistance under